2019
DOI: 10.1038/s41598-019-44660-y
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine-green-assisted near-infrared dental imaging - the feasibility of in vivo imaging and the optimization of imaging conditions

Abstract: X-ray-based imaging, including computed tomography, plays a crucial role in the diagnosis and surgery of impacted teeth that affects over 25% of the human population. But the greatest disadvantage of this technique is ionizing radiation risk to the patients. Here we describe a completely ionizing-radiation-free in vivo near-infrared (NIR) fluoresence dental imaging with indocyanine green (ICG) agent that has rarely been applied in dental imaging. Our method can acquire dental structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Indocyanine green (ICG), a FDA approved NIR organic dye, is used for intraoperative optical imaging in the clinic [22,23] and for dental imaging [24]. It is under investigation for imageguided PDT and, most recently, as a photosensitizer for combined PDT-PTT upon irradiation at 808 nm [25].…”
Section: Introductionmentioning
confidence: 99%
“…Indocyanine green (ICG), a FDA approved NIR organic dye, is used for intraoperative optical imaging in the clinic [22,23] and for dental imaging [24]. It is under investigation for imageguided PDT and, most recently, as a photosensitizer for combined PDT-PTT upon irradiation at 808 nm [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although application of PB is a feasible procedure, detection of fine (neo) vasculature system is often not possible due to its relatively low sensitivity by optical wave length-light. Hence, visualization and in vivo imaging by various dye injection is becoming frequently reported [ 21 24 ]. Injected PB after the current procedure showed the successful ligation and enlargement of the main L.V.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 In our previous research we demonstrated the feasibility of indocyanine green (ICG) for dental imaging in the rat model and human extracted tooth. [39][40][41][42][43][44] We found that ICF-NIR fluorescent (ICG-NIRF) imaging could diagnose several typical diseases in human extracted teeth, such as caries lesions, decay, and insidious caries. 42,43 In particular, we compared ICG-NIRF dental imaging with X-ray imaging.…”
Section: Introductionmentioning
confidence: 99%